Conflict of Norms Between Regional Regulations and Higher Legislation: Analysis of the Principle of Legal Hierarchy - Marudut Hasugian; Wibowo, Mustofa Ponco (Ipso Jure, 2026)
Conflicts between regional regulations and higher-level laws and regulations are a common problem in the Indonesian legal system and have implications for legal uncertainty. This study aims to analyze the application of the principle of legal hierarchy in resolving these normative conflicts and to identify the causal factors and effectiveness of the resolution mechanisms. The research method used is normative legal research with a statutory, conceptual, and case approach, supported by primary, secondary, and tertiary legal materials. The results of the study indicate that normatively, the principle of lex superior derogat legi inferiori has provided a strong basis for maintaining normative consistency, but its implementation still faces various obstacles, such as weak regulatory harmonization, limited capacity of regional regulation makers, and the influence of local political interests. In addition, conflict resolution mechanisms through judicial review by the Supreme Court and executive review by the central government have not been fully effective due to dualism of authority and implementation obstacles. This condition has an impact on regulatory disharmony, disrupted investment climate, and decreased public trust in the law. Therefore, it is necessary to strengthen preventive mechanisms through harmonization from the planning stage, integration of the supervisory system, and affirmation of the role of the principle of legal hierarchy as the main instrument in maintaining the consistency of the legal regulatory system in Indonesia.